Psychological factors in property crimes: theories, traits, and treatment - Deka, Dorothy Bhandari (Victimology, 2022)
Crime is mostly experienced as more serious than an accident or similar kind of misfortune. It is difficult to accept sometimes the fact that the loss and injury have been caused by the deliberate act of another human being. It might be difficult to predict how an individual will respond to a certain crime situation. Crime-related situations can be like crimes against a person; crime against property is an important division of crime along with other criminal acts. Crime against property such as extortion, robbery, or arson may be with or without force. It can be cheating, destruction, and taking property like stealing money. This chapter explains different types of crimes in general as well as against property and the causes. The risk factors, personality traits of the person executing the crime, the vulnerabilities of victims, and psychological reactions of victims will be discussed. The prevention methods, as well as interventions, will be described at length which will include actions to be taken by the individual level and society at large.